Prevalence and Risk Factor of Repeat Breeder Syndrome in Dairy Cows in KUD Bebarengan Anggayuh Tentrem Urip, Batu City, East Java Province - Frida Aulya Arningdiah; Rahmatullah, Aldin Akbar; Cindy Ercha Aulia Putri; Mufasirin; Hermin Ratnani; Rimayanti; Sri Pantja Madyawati; Tita Damayanti Lestari; Muhammad Al-Syafiq bin Abdul Halim; Nuurin Ajrin Karim (Media Kedokteran Hewan, 2024)
This study aims to contribute valuable insights to readers and serve as a reference for dairy farmers looking to enhance their operations. By examining the prevalence and risk factors associated with repeat breeder syndrome in dairy cows within the Village Unit Cooperation (KUD) Bebarengan Anggayuh Tentrem Urip, Batu City, East Java Province, this study aims to aid in preventing such occurrences and ultimately improve dairy cow productivity. The survey method was employed, utilizing data sourced from cooperative and farmer records, as well as observations, interviews, and questionnaire responses. Analysis revealed that out of 50 farmers owning a total of 281 cows, 30 farmers possessed a combined total of 58 dairy cows classified as repeat breeders. Consequently, the prevalence rate of repeat breeders among farmers was found to be 20.64%. Descriptive analysis was conducted on the collected data, with additional SPSS Chi-Square (X²) analysis performed to identify risk factors associated with repeat breeders. These risk factors include breeder experience, knowledge of reproduction and estrus phases, communication with artificial inseminators and veterinarians, housing conditions, as well as factors related to livestock feed and water.